Century 21 Accounting: Advanced, 11th Student Edition, 11th Edition - Claudia Bienias Gilbertson; Mark W. Lehman (Cengage Learning, 2019)
Transform your high school accounting course with CENTURY 21 ACCOUNTING: ADVANCED 11th, the leader in high school accounting education for more than 100 years. The Century 21 Series is known for its "Work Together" and "On Your Own" pedagogy that offers teachers a chance to model skills and provides students with multiple chances to practice and apply concepts while moving up Bloom's Taxonomy to analysis and evaluation. In addition, commercial technology is integrated throughout the text and equips students to work with a variety of commercial software programs such as, Microsoft Excel, Sage 50, or QuickBooks. Input from educators, accounting professionals, content experts, and high school accounting students has informed the eleventh edition's new critical-thinking activities, real-world applications, updated accounting instruction, and enhanced online learning solution, MindTap with Aplia Online Working Papers for Century 21 Accounting: Advanced, 11th. MindTap is the digital learning solution that helps teachers engage and transform today's students into critical thinkers. Through paths of dynamic Aplia Online Working Paper assignments, simulations, readings, study tools that you can personalize, MindTap helps you turn cookie cutter into cutting edge, apathy into engagement, and memorizers into higher-level thinkers. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.